Control over linear pulse systems - Akhmetov, M. U.; Perestyuk, N. A.; Tleubergenov, M. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Rank conditions for control of linear pulse systems are established. The Pontryagin maximum principle is obtained in sufficient form. An example of control synthesis in a problem for linear pulse systems is given.